Output maximization container loading problem with time availability constraints - Pedro B. Castellucci; Franklina Maria Bragion de Toledo; Alysson Machado Costa (Operations Research Perspectives, 2019)
Research on container loading problems has helped increase the occupation rate of containers in different practical situations. We consider these problems within a context which might pressure the loading process, leading to sub-optimal solutions. Some facilities like cross-docks have reduced storage space which might force early loading activities. We propose a container loading problem which accounts for this limited storage by explicitly considering the schedule of arrival for the boxes and the departure time of the trucks. Also, we design a framework which handles the geometric and temporal characteristics of the problem separately, enabling the use of methods found in the literature for solving the extended problem. Our framework can handle uncertainty in the schedule and be used to quantify the impact of delays on capacity utilization and departure time of trucks.
Keywords: 330; Container loading; Cross-docking; Packing; Stochastic dynamic programming